2023
DOI: 10.1111/bph.16218
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterisation of erenumab, Aimovig, at two calcitonin gene‐related peptide responsive receptors

Abstract: Background and PurposeCalcitonin gene‐related peptide (CGRP) is involved in migraine pathophysiology. CGRP can signal through two receptors. The canonical CGRP receptor comprises the calcitonin receptor‐like receptor (CLR) and receptor activity‐modifying protein 1 (RAMP1); the AMY1 receptor comprises the calcitonin receptor (CTR) with RAMP1. Drugs that reduce CGRP activity, such as receptor antagonists, are approved for the treatment and prevention of migraine. Despite being designed to target the canonical CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 64 publications
(159 reference statements)
0
1
0
Order By: Relevance
“…Our recent structural work revealed that activation of AMYRs by the 32-amino-acid CTs is distinct from that by the 37-amino-acid rAmy and that the orientation of the AMY 1 R ECD when bound to sCT differs to that when bound to rAmy, or CGRP as observed in the current study. More recent studies revealed that erenumab could bind competitively with longer peptide agonists, such as rAmy or CGRP, at AMY 1 R. Overlay of the CGRP–AMY 1 R complex and the erenumab-bound CGRP ectodomain structure (PDB: 6UMG) revealed that the binding of erenumab is likely to be influenced by the orientation of the ECD of the receptors, in addition to residue-specific interactions (Figure C). This provides a rationale for the ability of erenumab to inhibit Amy and CGRP, but not CT binding to AMY 1 R, as well as providing an additional mechanism for its lack of AMR antagonism, as both AM 1 R and AM 2 R have distinct ECD orientations to the CGRPR …”
Section: Resultsmentioning
confidence: 99%
“…Our recent structural work revealed that activation of AMYRs by the 32-amino-acid CTs is distinct from that by the 37-amino-acid rAmy and that the orientation of the AMY 1 R ECD when bound to sCT differs to that when bound to rAmy, or CGRP as observed in the current study. More recent studies revealed that erenumab could bind competitively with longer peptide agonists, such as rAmy or CGRP, at AMY 1 R. Overlay of the CGRP–AMY 1 R complex and the erenumab-bound CGRP ectodomain structure (PDB: 6UMG) revealed that the binding of erenumab is likely to be influenced by the orientation of the ECD of the receptors, in addition to residue-specific interactions (Figure C). This provides a rationale for the ability of erenumab to inhibit Amy and CGRP, but not CT binding to AMY 1 R, as well as providing an additional mechanism for its lack of AMR antagonism, as both AM 1 R and AM 2 R have distinct ECD orientations to the CGRPR …”
Section: Resultsmentioning
confidence: 99%